Sejarah Masuknya Islam Ke Nusantara dan Proses Islamisasi di Nusantara - Elva Samrotul Azizah; Shefira Nurrahma Sari; Nik Haryanti (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The process of Islam entering the archipelago has a long and interesting history to study. It is estimated that Islam entered the archipelago in the 7th century AD to the 13th century AD. The process of Islamization in the archipelago took place peacefully, where its spread emphasized the spiritual and ethical aspects of life, so that society could accept it well. The routes used were also very diverse, ranging from trade, marriage, politics to art and culture. In addition to these routes, the spread of Islam was also supported by the role of Islamic kingdoms such as the Samudra Pasai Kingdom, the Aceh Kingdom to the Demak Kingdom. With various routes and roles of the kingdom, Islam developed and took root in the archipelago. However, when Islam actually entered the archipelago is still a question to this day. These theories have historical evidence that supports their opinions, so that various theories have developed that explain the beginning of Islam entering the archipelago. These theories include the Gujarat Theory, the Arab Theory, the Persian Theory and the Chinese Theory.